Education of the patient and the patient´s family as one of the components of the intervention program for prevention of fall of hospitalized patients - Hajduchová, Hana; null, null; Brabcová, Iva; Tóthová, Valérie; Bártlová, Sylva; Doseděl, Martin (STEF92 Technology Ltd., 2018)
Fall-endangered patients, as well as their family should be informed on the reasons and ways of fall, on measures reducing the risk of fall, on undesirable effects of the medicines prescribed (e.g. due to the sleepiness and dizziness they cause), on the use of locomotory aids, on the use of signalling devices. The patients' involvement in their own health care seems indispensable. The patients are not only passive recipients of care, but they play an important role in assuring their own safety. The care for the patient should involve also the patient's family who should be offered sufficient information. The nurse should be able to make use of the information acquired from the family and educate the family on the strategy to reduce the occurrence of falls. The goal of this paper will consist in presenting one of the outcomes of the project called Analysis of factors influencing the risk of falls - potential involvement of nurses and pharmacists in minimization of the risk, implemented by the Faculty of Health and Social Sciences of the University of South Bohemia in České Budějovice and the Faculty of Pharmacy of Charles University in Hradec Králové in the Czech Republic.
Keywords: EDUCATION; INTERVENTION PROGRAM; FALL; HOSPITALIZED PATIENTS, NURSE